Genre-Based Instruction and Iranian EFL Learners’ Argumentative Essay writing: Performance, Structure, Perceptions, and Authorial Identity in Focus - Parastoo Alizadeh Oghyanous; Morteza Bakhtiarvand (Randwick International of Education and Linguistics Science Journal, 2024)
The current mixed methods study was an attempt to approach genre-based instruction from a fourfold perspective. As for the quantitative phase, first, it was aimed to examine the effect of genre-based instruction (GBI) on EFL learners’ argumentative essay writing performance. Second, the study investigated the overall organizational structure of learners’ argumentative essays in control and experimental groups. The participants of the study were 71 learners selected out of an initial number of 95 chosen based on convenience sampling. The selected 71 learners were divided into two groups of 35 and 36 who were assigned to the control and experimental group, respectively. Then, a writing pretest was administered to the two groups. After the treatment, the participants in both groups were given a writing posttest. The quantitative findings indicated that GBI was significantly effective on learners’ argumentative writing performance. Additionally, the quantitative structure analysis showed that the number of the argumentative essay elements in the essays of the experimental group was higher than those of the control group. Afterwards, ten participants in the experimental group were interviewed to seek their perceptions towards the efficacy of GBI in teaching argumentative essay writing and their authorial identity construction. The qualitative analysis of the interviews pointed to the learners’ positive attitudes towards GBI and the usefulness of this type of instruction for improving their argumentative writing performance. Finally, the ten participants in the experimental group reported their positive perceptions with regard to their authorial identity construction.